Images du corps nikkei à São Paulo - Helena Prado (Ateliers d'Anthropologie)
This article explores images relating to the Japanese population in São Paulo, based on the study of stereotyped representations and race determinants existing in collective discourse. By considering a few common expressions from popular language and by examining recorded discourse, it aims to analyse what is presented as obvious: the body designated as “Japanese” in Brazil, one that is foreign, different and excluded from the body representations at work in the “national myth”.It will therefore be a matter of identifying the phenotypical markers at play, and showing what directly follows from them, namely a series of representations “naturally” associated with the Nikkei ethnicity, having to do with norms of aesthetics and social behaviour, with moral and intellectual values, and with collective and individual practices expected from Japanese Brazilians.